Muhammed Fadil Al- Jamally and His role in Tunisia’s independence (1956) - Jameel, Rasha (Al-Adab Journal, 2025)
History tells us many stories and tales about men who left a clear imprint on the lives of their people and their country, and Iraq was one of them, as it was full of many important stations, especially in the diplomatic field, which represented the important will in foreign policy and the main axis of serving national interests and highlighting its civilized image through national figures who had a prominent role in that path. Muhammad Fadhil Al-Jamali is one of these and the most prominent of them in the royal era (1921-1958), who had an important role in the fields of politics, diplomacy, education and teaching in Iraq.